A novel organic‐inorganic flame retardant of ammonium polyphosphate chemically coated by Schiff base‐containing branched polysiloxane for polyamide 6. (9th July 2020) - Fan, Shuo; Sun, Yanlu; Wang, Xueli; Yu, Jianyong; Wu, Dequn; Li, Faxue
Abstract : A novel organic‐inorganic flame retardant (SP‐APP) was first designed by coating ammonium polyphosphate (APP) with Schiff base‐containing branched polysiloxane via ion exchange reaction and dehydration‐condensation. High water resistance and charring capacity of the SP‐APP greatly overcame the poor water resistance of APP and endowed polyamide 6 (PA6) with excellent flame retardancy and anti‐dripping. The prepared PA6/SP‐APP composite with 12 wt% of SP‐APP reached the highest limited oxygen index (LOI) of 32.5% and passed V‐0 rating of UL‐94 test with non‐dripping, while PA6 and PA6/APP with 12 wt% of APP failed to pass the UL‐94 test. A sharp reduction of 50.9% in peak heat release rate (PHRR) and 29.4% in total heat release (THR) was found for PA6/SP‐APP in contrast with PA6. The working mechanism of SP‐APP in enhancing the flame retardancy of PA6 was also explored intensively and the synergistic effects of catalytic degradation of APP, self‐crosslinking behavior of Schiff base structure and thermo‐oxidative degradation of branched polysiloxane contributed to the improvement of flame retardancy of PA6/SP‐APP.